2012
DOI: 10.1093/pubmed/fds099
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing investments in public health: a multi-criteria decision analysis

Abstract: This paper demonstrates that it is possible to incorporate criteria other than cost-effectiveness in the prioritization of public health investment using an MCDA approach. There are numerous approaches available that adopt the MCDA framework. Further research is required to determine the most appropriate approach in different settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 9 publications
1
58
0
7
Order By: Relevance
“…A number of studies suggested that some of the most influential evidence on local public health decision-making was generated through local evaluation activities [40, 41, 55]. Such data meet decision-makers’ requirements around the locality of evidence and are generated within the local political context therefore meeting requirements around the transferability of findings [40, 47].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies suggested that some of the most influential evidence on local public health decision-making was generated through local evaluation activities [40, 41, 55]. Such data meet decision-makers’ requirements around the locality of evidence and are generated within the local political context therefore meeting requirements around the transferability of findings [40, 47].…”
Section: Resultsmentioning
confidence: 99%
“…8 These figures are in line with those for other public health interventions such as smoking cessation and statins for primary prevention of cardiovascular disease. 9 Economic analysis for NICE confirms that the financial outlay for surgery is justified for the NHS. 10 In patients with diabetes, for example, the cost of surgery will be recouped within three years through reduced prescriptions.…”
Section: Effectiveness Of Surgerymentioning
confidence: 94%
“…*50 Goetghebeur et al, 2008;Goetghebeur et al, 2010;Goetghebeur et al, 2012;Hofmann, 2005;Lehoux & Williams-Jones, 2007;Miot et al, 2012;Tony et al, 2011. *51 Golan & Hansen, 2010;Johnson et al, 2009;Kapiriri et al, 2009;Mullen, 2004. *52 Browman et al, 2008;Dionne et al, 2015;Mullen, 2004. *53 Kirby et al, 2008;Marsh et al, 2013;Wilson et al, 2007. *54 Diaby & Goeree, 2014;Golan & Hansen, 2012;Hofmann, 2005;Johnson et al, 2009;Lehoux & Williams-Jones, 2007;Tannahill, 2008;Thokala & Duenas, 2012;Venhorst et al, 2014;Vuorenkoski et al, 2008;Youngkong et al, 2012b. *55 Mullen, 2004;Tannahill, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…*19 Hofmann, 2005Lehoux & Williams-Jones, 2007;Menon et al, 2010;Tannahill, 2008. *20 Golan & Hansen, 2010;Hummel et al, 2012;Martin et al, 2001;Mühlbacher & Kaczynski, 2015;Mullen, 2004;Wilson et al, 2006;Wilson et al, 2009. *21 Goetghebeur et al, 2010;Gurtner, 2014;Menon et al, 2010;Tannahill, 2008. *22 Andreae et al, 2009;Baltussen et al, 2007;Defechereux et al, 2012;Diaby & Goeree, 2014;Dionne et al, 2015;Goetghebeur et al, 2008;Goetghebeur et al, 2010;Goetghebeur et al, 2012;Golan & Hansen, 2010;Jehu-Appiah et al, 2008;Kolasa et al, 2016;Koopmanschap et al, 2010;Miot et al, 2012;Simoens, 2014;Tony et al, 2011;Vuorenkoski et al, 2008;Youngkong et al, 2009. *23 Andreae et al, 2009;Duthie et al, 1999;Ghaffar, 2009;Johnson et al, 2009;Menon et al, 2010;Noorani et al, 2007;Tromp & Baltussen, 2012;Wilson et al, 2007;Youngkong et al, 2009;Youngkong, 2014. *24 Marsh et al, 2013;…”
Section: (("Decision Making"[mesh] Not Shar*[tiab]) or ("Decision Supunclassified
See 1 more Smart Citation